Strategic Navigation of Educational Institutions: Implementation of External Audit and EFE Matrix in Facing Global Disruption - Rofiq Noorman Haryadi; Imam Mujahid; Usman Abu Bakar (Pasundan Social Science Development, 2026)
Higher education institutions currently face global turbulence caused by demographic shifts, economic instability, regulatory policies, and digital technology disruption. This study aims to formulate the institution's strategic position in anticipating external challenges through an outside-in strategic management approach. The method used is descriptive analysis through a comprehensive literature review, integrating secondary data from contemporary management literature. Data evaluation is systematically processed using three main instruments: Porter's Five Forces Model, the External Factor Evaluation (EFE) Matrix, and the Competitive Profile Matrix (CPM). The external audit results indicate the presence of ten actionable variables, with the threat of substitute products such as non-degree certification and declining new student input being the most destructive challenges to the traditional education model. Based on the quantitative analysis, the institution obtained a total EFE score of 2.51. This figure indicates that the institution's strategic response is in the average category; the current strategy is quite effective in exploiting opportunities but remains vulnerable to external competitors. Meanwhile, the CPM analysis confirms that despite advantages in tuition fees and location, institutions lag significantly behind their main competitors in terms of the quality of their digital facilities. The study concludes that institutions can no longer rely solely on internal operational efficiency. Managers and educators are required to immediately move beyond their routine operational comfort zones, fundamentally reposition their values, and aggressively accelerate digital transformation. Aligning internal capacity with external dynamics is an absolute prerequisite for maintaining relevance and achieving sustainable competitive advantage.